HUBUNGAN TINGKAT PENGETAHUAN DAN SIKAP REMAJA DALAM PENCEGAHAN KTD DI DESA MEKARWANGI, CIKARANG BARAT, BEKASI - Nadia Sabrina Putri; Widy Nurwiandani; Era Revika; Riadini Wahyu Utami (JHN: Journal of Health and Nursing, 2026)
Unintended pregnancy among adolescents is a reproductive health issue with serious physical, psychological, social, and educational consequences. Adolescent knowledge and attitudes play a crucial role in efforts to prevent unintended pregnancies. This study aimed to understand the relationship between knowledge levels and attitudes regarding the prevention of unintended pregnancies among adolescents in Mekarwangi Village, West Cikarang, Bekasi. This quantitative study employed a cross-sectional design involving 157 adolescents aged 14–19 years, selected via purposive sampling. Data were collected using a structured questionnaire that had undergone validity and reliability testing, and were subsequently analyzed using the Chi-Square test (α = 0.05). The results showed that the majority of respondents possessed good knowledge (89.8%) and a positive attitude (8.7%). However, the Chi-Square test yielded a significance value of 0.641 (≥ 0.05), indicating no significant relationship between adolescent knowledge and attitudes regarding the prevention of unintended pregnancies. Good knowledge is not always accompanied by a positive attitude. Therefore, reproductive health education programs are needed that not only expand knowledge but also shape attitudes and behaviors conducive to preventing unintended pregnancies.